corporate governance in the Islamic banking industry - Susanto, Rosya Mawaddah (Maliki Interdisciplinary Journal, 2023)
Currently Islamic banks are considered as an alternative way for people to save funds safely, calmly and peacefully. Because Islamic banks themselves offer different offers from conventional banks, where Islamic banks carry out their operations in accordance with the provisions of Islamic law. So that customers from Islamic banks feel confident in using services or products from Islamic banks. Thus, Islamic banks need to maintain their operational systems in order to avoid things that are prohibited by Islamic law. In addition to the operational system, Islamic banks also need to emphasize Good Corporate Governance (GCG). Bank Internal Audit is important in improving the implementation of Good Corporate Governance (GCG), where Good Corporate Governance (GCG) is a demand from society and also a reflection of the performance of an organization. The Bank's internal auditors (Internal Control) have a significant and positive effect on the implementation of good governance in Islamic Banking. This explains that the more effective the implementation of internal audit and the stronger the internal control that is built, the higher the implementation of good governance in Islamic Banking will be. Thus, in Islamic banking, Bank Internal Audit is needed to create effective Good Corporate Governance (GCG) principles and objectives.